Core and surface microgel mechanics are differentially sensitive to alternative crosslinking concentrations - Mohapatra, Himansu (Soft Matter, 2017)
Microgel mechanics are central to the swelling of stimuli-responsive materials and furthermore have recently emerged as a novel design space for tuning the uptake of nanotherapeutics. Despite this importance, the techniques available to assess mechanics, at the sub-micron scale, remain limited. In this report, all mechanical moduli for a series of air-dried, polystyrene-co-poly(N-isopropylacrylamide) (pS-co-NIPAM) microgels of varying composition in monomer and crosslinker (N,N′-methylene-bisacrylamide (BIS)) mol% have been determined using Brillouin light scattering (BLS) and AFM nanoindentation. These techniques sample the material through distinct means and provide complementary nanomechanical data. An initial demonstration of this combined approach is used to evaluate size-dependent nanomechanics in pS particles of varying diameter. For the pS-co-NIPAM series, our BLS results demonstrate an increase in Young’s (E) and shear moduli with increasing NIPAM and/or BIS mol%, while the Poisson’s ratio decreased. The same rank order in E was observed from AFM and the two techniques correlate well. However, at low BIS crosslinking, an inverted particle structure persists and small increases in BIS yield a higher increase in E from AFM relative to BLS, consistent with a higher density at the particle surface. At higher BIS incorporation, the microgel reverts to a typical, dense-core structure and further increasing BIS yields changes to core-particle mechanics reflected in BLS. Lastly, at 75 mol% NIPAM, the microgels displayed a broad volume phase transition and increased crosslinking resulted in a minor, yet unexpected, increase in swelling ratio. This complementary approach offers new insight into nanomechanics critical for microgel design and application.